Private international law in contractual disputes - Ahmad, Muhamad Hassan; Abu Backer, Hamid Sultan; Lilienthal, Gary; Ali Mohamed, Ashgar Ali; Masum, Ahmad (CLJ Malaysia Sdn Bhd, 2024)
This chapter mainly discusses the application of “private international law” – also referred to as the “conflict of laws”1 – in contractual disputes. This subject, in essence, is related to three major factors in deciding a civil case which involves foreign elements, such as, which forum has the jurisdiction to try the case; the law of which State is applicable to legal issues; and the issues related to recognition of foreign judgments.